(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
General Insurance is typically defined as any insurance that is not determined to be life insurance but “General Insurance comprises of insurance of property against fire, burglary etc and personal insurance such as Accident and Health Insurance and liability insurance which covers legal liabilities”[1]. “There are also other covers such as Errors and Omissions insurance for professionals, credit insurance” [1]. “General Insurance acts as aegis to the financial causalities and alongside it also acts an economical back-up for a nation’s economy” [2].Insurance allied up with banking sector dispenses up to 7% of India’s total GDP. Till date we have observed foreign insurance companies engaging into Indian markets and having share of 24% of FDI being allowed in the Indian market.